Source Parameters of the 2005 Mw 7.2 Miyagi-Oki, Japan, Earthquake as Inferred from Teleseismic P-Waves - Ruey-Der Hwang; Tzu-Wei Lin; Guey-Kuen Yu; Jo-Pan Chang; Wen-Yen Chang (Terrestrial, Atmospheric and Oceanic Sciences, 2010)

(untitled)
We investigate the fault parameters of the 2005 Miyagi-Oki (Japan) earthquake using duration variations of teleseismic P-waves. The results show that the earthquake has a thrust-type mechanism and a seismic moment of 4.46 ¡_ 1019 Nm. Rupture directivity analysis suggests that the earthquake occurred as a result of a bilateral faulting on the fault plane with a strike of 247¢X, a dip of 17¢X and a slip of 125¢X. The optimal rupture azimuth, measured counterclockwise from the strike on the fault plane, is 170¢X (or 350¢X). The rupture length and average source duration are estimated to be 73.4 km and 14.5 sec, respectively. Thus the rupture velocity is 2.53 km sec-1 (~0.57 times the value of S-wave velocity), which is lower than the value for other similarly sized earthquakes. This implies that the 2005 Miyagi-Oki earthquake was probably a slow event. Consequently, there may have been less release of high-frequency seismic energy, leading to lower radiated seismic energy and radiation efficiency (~0.32 - 0.48). In other words, relatively larger fracture energy occurred during earthquake faulting in addition to the heat due to friction. The ratio of the static stress drop to the apparent stress (> 2.0) also suggests that the earthquake can be modeled as a frictional overshoot in a stress model, which implies the transformation of a lower percentage of strain energy into seismic-wave energy during the process of earthquake rupturing.